DO TEACHER COMPETENCE, LEARNING ENVIRONMENT, AND ACADEMIC STRESS SIGNIFICANTLY INFLUENCE STUDENT LEARNING OUTCOMES IN ISLAMIC JUNIOR HIGH SCHOOLS ? - Hasmi Nur Bayhaqi; Didit Darmawan (Program Studi PGSD Universitas Flores, 2025)
This study aims to examine the significant influence of teacher competence, the learning environment, and academic stress on the learning outcomes of students at MTs Bi’rul Ulum, Gemurung, Gedangan, Sidoarjo. A quantitative survey method was employed with a population of 115 students, all of whom were included as research subjects using a total sampling technique. The data were analyzed using multiple regression analysis. The findings revealed that teacher competence has a significant positive effect on students' learning outcomes, the learning environment showed no significant effect, while academic stress had a significant influence on learning outcomes at MTs Bi’rul Ulum. These results imply that the school should improve teacher competence not only through technical training but also by applying humanistic methods like storytelling to enhance emotional engagement. While the learning environment showed no significant effect, fostering a positive atmosphere and managing academic stress through Islamic values such as ikhtiar and tawakkal remain essential to support motivation and learning outcomes. The findings of this study highlight academic stress as the most dominant factor, which is reconceptualised not just as a negative burden but as a source of positive motivation (eustress). The study provides a new perspective by viewing academic stress as motivation with spiritual value and in the learning process. This study explores how teacher competence, learning environment and academic stress affect student learning outcomes in Islamic junior high schools. This is a new area of research. The study provides new insights for the development of educational strategies in Islamic schools.